1980
DOI: 10.1111/j.1365-2621.1980.tb02607.x
|View full text |Cite
|
Sign up to set email alerts
|

NUTRITIVE VALUE OF TRITICALE AND THE EFFECTS OF ITS SUPPLEMENTATION TO WHEAT AND BENGAL GRAM (Cicer arietinum) FLOUR

Abstract: The object of the investigation 'was to study the nutritive value of triticale and to ascertain the effect of its supplementation to wheat and bengal gram, flours. The different flours were analysed for lysine, methionine, and cystine content. Protein and lysine contents .of triticale flour were higher as compared to wheat flour. The blend of wheat flour and triticale flour in the ratio 60:40 for the preparation of chap&i (unleavened bread) was found acceptable. Acceptability of the chapafi was slightly improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…For copper (6 to 10 pg/g) and manganese (28 to 38 pg/g) the differences were found to be non-significant. Variations in mineral contents of triticale grain were also evidenced by other workers [l, 4, 101. In fact, triticale seems to have more minerals as compared to wheat, which can be supported by the results of KHAN et al [5], SINGH et al [2] and JUNEJA et al [6]. It is difficult to draw a definite conclusion regarding the trace elements, i. e. zinc, copper, iron and manganese contents, between triticale and the two wheat varieties.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…For copper (6 to 10 pg/g) and manganese (28 to 38 pg/g) the differences were found to be non-significant. Variations in mineral contents of triticale grain were also evidenced by other workers [l, 4, 101. In fact, triticale seems to have more minerals as compared to wheat, which can be supported by the results of KHAN et al [5], SINGH et al [2] and JUNEJA et al [6]. It is difficult to draw a definite conclusion regarding the trace elements, i. e. zinc, copper, iron and manganese contents, between triticale and the two wheat varieties.…”
Section: Resultsmentioning
confidence: 86%
“…The changes in mineral distribution caused by the milling of grains into flour, short and bran of triticale has been reported by LORENZ et al [3]. The distribution of trace elements in triticale whole grain and milled fractions has been studied by JONES [4].The mineral contents of triticale and wheat were compared by KHAN et a1 [5], SINGH et al [2], and JUNEJA et al [6], who reported that most of the mineral conteqts were found to be higher in triticale than wheat. The flour had a lower amount of mineral contents than that of whole grain [7].…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Cereal grains form a staple food of the majority of the people in the developing countries and provide between 70-80% of total calories (252 calories /l00gm) and more than 66% of protein in the diet (Juneja et al, 1980). Wheat is an important cereal because it can be used for preparation of many products, bread is one of the least expensive most important staples in the world, because of their high popularity and large consuming, bakery products (including bread) could be a vehicle to improve the quality and nutritive value, bread considered the one of the simplest food manufactured, and its characteristics may differ from country to country (Abreu et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Fortification of breads with legumes has enhanced their nutritional quality (Juneja, Kawatra & Bajaj, 1980;El-Minyawi & Zabik, 1981;Nmorka & Okezie, 1983).…”
Section: Introductionmentioning
confidence: 99%